2018
DOI: 10.1155/2018/7969068
|View full text |Cite
|
Sign up to set email alerts
|

Roles of NUCKS1 in Diseases: Susceptibility, Potential Biomarker, and Regulatory Mechanisms

Abstract: Nuclear casein kinase and cyclin-dependent kinase substrate 1 (NUCKS1) is a 27 kD chromosomal, highly conserved, and vertebrate-specific protein. NUCKS1 gene encodes a nuclear protein and the conserved regions of NUCKS1 contain several consensus phosphorylation sites for casein kinase II (CK2) and cyclin-dependent kinases (Cdk) and a basic DNA-binding domain. NUCKS1 is similar to the high mobility group (HMG) family which dominates chromatin remodeling and regulates gene transcription. Meanwhile, NUCKS1 is a R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 65 publications
0
21
0
1
Order By: Relevance
“…NUCKS1 is similar to the high mobility group (HMG) family, which dominates chromatin remodeling and regulates gene transcription [7]. NUCKS1 plays a significant role in various diseases as susceptibility or potential marker and involve in several regulatory mechanisms [8-12] Noticeably, NUCKS1 involves in cell growth and proliferation as well as in DNA repair [13]. Using genome wide Association Studies (GWAS) it was found that NUCKS1 is a susceptibility gene for many diseases and a single disease can be associated with multiple SNPs of NUCKS1.…”
Section: Introductionmentioning
confidence: 99%
“…NUCKS1 is similar to the high mobility group (HMG) family, which dominates chromatin remodeling and regulates gene transcription [7]. NUCKS1 plays a significant role in various diseases as susceptibility or potential marker and involve in several regulatory mechanisms [8-12] Noticeably, NUCKS1 involves in cell growth and proliferation as well as in DNA repair [13]. Using genome wide Association Studies (GWAS) it was found that NUCKS1 is a susceptibility gene for many diseases and a single disease can be associated with multiple SNPs of NUCKS1.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, rs823114, with the 7th lowest p-value (4.35x10-09), and a less significant SNP, rs7536483, are located in the promoter of NUCKS1 (Nuclear casein kinase and cyclin-dependent kinase substrate 1). NUCKS1 is a chromatin-associated protein with a role in the DNA damage response, DNA repair, metabolism, and inflammatory and immune responses, but its overall function is still unknown [36]. Other than rs4889599, we observed that these SNPs are located in ATAC-peaks that are flanked by H3K27ac ChIP-seq peaks.…”
Section: Finding Candidate Functional Snpsmentioning
confidence: 77%
“…Following the TSP pathway is NUCKS1, this gene codes for nuclear casein kinase and cyclin-dependent kinase substrate 1 [ 77 ]. NUCKS1 is a nuclear protein, highly conserved in vertebrates [ 78 ]. It is expressed in most tissues and experiments in rats have shown that its expression increases during the initial stages of embryonic development in brain and liver [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al [ 79 ] reported that in the embryonic development, NUCKS1 appears to be a marker for migrating cells of the neural crests. NUCKS1 has been shown to be important for homologous recombination DNA damage response [ 80 ] and to play a role in inflammatory immune response [ 78 ]. It is interesting to note that the NUCKS1 product is also used by the HIV-1 for the viral transcription of its genetic material [ 81 ] and has been reported as a biomarker for some cancer [ 82, 83 ].…”
Section: Discussionmentioning
confidence: 99%